Protection of Personal Data in Criminal Law Enforcement Processes - Sintong Gariel Lumban Tobing; T. Riza Zarzani (PT. Sinergi Legal Publisher, 2025)
This study aims to determineHow is Personal Data Protection in the Criminal Law Enforcement Process? The research methodology used in this study is normative juridical research using a statute approach, a conceptual approach, and a case approach. The results of the discussion stated that the regulations regarding Personal Data in Indonesia are regulated in Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) which was ratified on Tuesday, September 20, 2022. If there is a failure in Personal Data Protection, Administrative Sanctions will be imposed under Article 57 and Criminal Provisions under Article 67 and Article 69. In the case of criminal acts, Article 70 will be imposed.